Human papillomavirus (HPV)-16/18 AS04-adjuvanted vaccine for the prevention of cervical cancer and HPV-related diseases. (3rd March 2016) - Skinner, S. Rachel; Apter, Dan; De Carvalho, Newton; Harper, Diane M.; Konno, Ryo; Paavonen, Jorma; Romanowski, Barbara; Roteli-Martins, Cecilia; Burlet, Nansa; Mihalyi, Attila; Struyf, Frank
ABSTRACT: Vaccines are available against human papillomavirus (HPV), the causal agent of cervical and other cancers. Efficacy data from the HPV-16/18 AS04-adjuvanted vaccine clinical trial program were reviewed. Six randomized, controlled phase II/III trials evaluating cervical endpoints enrolled women from diverse populations and geographical locations. The program analyzed extensively the cohorts most relevant from a public health perspective: the total vaccinated cohort (TVC), approximating a general population including those with existing or previous HPV infection, and TVC-naïve, approximating a population of young women before sexual debut. Results show that the vaccine reduces HPV-16/18 infection and associated cervical endpoints in women regardless of age, location, or sexual experience. It provides cross-protection against some non-vaccine oncogenic HPV types and types causing genital warts, and may be effective against vulvar, oral, and anal HPV infection. Early epidemiology data following its introduction suggest a decline in the prevalence of vaccine and some non-vaccine HPV types.